Quorum Sensing Signaling and Quenching in the Multidrug-Resistant Pathogen Stenotrophomonas maltophilia - Huedo, Pol; Coves, Xavier; Daura, Xavier; Gibert, Isidre; Yero, Daniel (Frontiers in Cellular and Infection Microbiology, 2018)
Stenotrophomonas maltophilia is an opportunistic Gram-negative pathogen with increasing incidence in clinical settings. The most critical aspect of S. maltophilia is its frequent resistance to a majority of the antibiotics of clinical use. Quorum Sensing (QS) systems coordinate bacterial populations and act as major regulatory mechanisms of pathogenesis in both pure cultures and poly-microbial communities. Disruption of QS systems, a phenomenon known as Quorum Quenching (QQ), represents a new promising paradigm for the design of novel antimicrobial strategies. In this context, we review the main advances in the field of QS in S. maltophilia by paying special attention to DSF (Diffusible Signal Factor) signalling, AHL (Acyl Homoserine Lactone) responses and the controversial Ax21 system. Advances in the DSF system include regulatory aspects of DSF synthesis and perception by both rpf-1 and rpf-2 variant systems, as well as their reciprocal communication. Interaction via DSF of S. maltophilia with unrelated organisms including bacteria, yeast and plants is also considered. Finally, an overview of the different QQ mechanisms involving S. maltophilia as quencher and as object of quenching is presented, revealing the potential of this species for use in QQ applications. This review provides a comprehensive snapshot of the interconnected QS network that S. maltophilia uses to sense and respond to its surrounding biotic or abiotic environment. Understanding such cooperative and competitive communication mechanisms is essential for the design of effective anti QS strategies.